2017
DOI: 10.1016/j.kint.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Kidney fibroblast growth factor 23 does not contribute to elevation of its circulating levels in uremia

Abstract: Fibroblast growth factor 23 (FGF23) secreted by osteocytes is a circulating factor essential for phosphate homeostasis. High plasma FGF23 levels are associated with cardiovascular complications and mortality. Increases of plasma FGF23 in uremia antedate high levels of phosphate, suggesting a disrupted feedback regulatory loop or an extra-skeletal source of this phosphatonin. Since induction of FGF23 expression in injured organs has been reported we decided to examine the regulation of FGF23 gene and protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 62 publications
1
52
0
Order By: Relevance
“…In normal rodents, these authors showed that kidneys removed FGF23 from the renal circulation [17]. In rats subjected to 5/6 nephrectomy, they found that renal arterial and venous concentrations of FGF23 were comparable even though renal synthesis of FGF23 was demonstrable, and concluded that net renal addition of FGF23 to the circulation had not occurred [18]. The authors also documented FGF23 gene transcription in skeletons of animals receiving normal- or high-phosphate diets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In normal rodents, these authors showed that kidneys removed FGF23 from the renal circulation [17]. In rats subjected to 5/6 nephrectomy, they found that renal arterial and venous concentrations of FGF23 were comparable even though renal synthesis of FGF23 was demonstrable, and concluded that net renal addition of FGF23 to the circulation had not occurred [18]. The authors also documented FGF23 gene transcription in skeletons of animals receiving normal- or high-phosphate diets.…”
Section: Discussionmentioning
confidence: 99%
“…Total parathyroidectomy eliminated FGF23 gene transcription in bone, and it greatly reduced plasma [FGF23]. The authors concluded that PTH promoted skeletal synthesis of FGF23 in rodents with remnant kidneys, and high [FGF23] resulted from decreased renal extraction of the hormone [18]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In uremic animals, renal FGF23 expression correlates with local TGF-β1 expression [112]. Smith et al demonstrated that FGF23 augments FGFR4 activation and upregulation of the calcium transporter in the absence of klotho, leading to enhanced TGF-β1 autoinduction through increases of both intracellular calcium and mitochondrial reactive oxygen species [113].…”
Section: Possible Role Of Tgf-β In Chronic Kidney Disease-mineral mentioning
confidence: 99%
“…However, the role of kidney as a probable extraskeletal source of FGF-23 remains controversial. Thus, induced expression of FGF-23 has been reported in animal models of CKD [9,10] whereas a very recent study showed that kidney FGF-23 does not contribute to elevation of its circulating levels in uremia [11].…”
mentioning
confidence: 99%